Pengaruh Viral Marketing, Etika Bisnis, dan Online Customer Review Terhadap Keputusan Pembelian dalam Perspektif Ekonomi Islam (Studi Kasus pada Pembeli Bakso Goreng Raja Ngemil di Marketplace Shopee) - Amalia, Dinda Dwi; Syihabudin; Fakhrudin, Muhamad (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
This research aims to analyze the influence of viral marketing, Islamic business ethics, and online customer reviews in influencing purchasing decisions for Bakso Goreng Raja Ngemil. The sampling technique used in this research uses the Cochran formula because the population size is not known with certainty with the number of respondents being 102 people using a Likert scale measuring instrument. The analysis tool used is SPSS 25.0. The research results show that 1) Viral marketing has a positive and significant effect on purchasing decisions, 2) Islamic business ethics has a positive and significant effect on purchasing decisions, 3) Online Customer Reviews has a positive and significant effect on purchasing decisions. Keyword: Islamic Business Ehicsm, Online Customer Review, Purchase Decisions, Viral Marketing